1978
DOI: 10.1093/nar/5.10.3603
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of inner histone-DNA complexes

Abstract: Chicken-erythrocyte inner histone tetramer has been complexed with several natural and synthetic DNA duplexes by salt-gradient dialysis at various protein/DNA ratios. The resulting complexes, in low-ionic-strength buffer, have been examined by electron microscopy, circular dichroism, and thermal denaturation. Electron microscopy reveals nucleosomes (v bodies) randomly arranged along DNA fibers, including poly(dA-dT)*poly(dA-dT), poly(dI-dC)*poly(dI-dC), but not poly(dA)*poly(dT).Circular dichroism studies show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

1981
1981
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 22 publications
(19 reference statements)
2
16
0
Order By: Relevance
“…This region appears to be devoid of nucleosomes as shown by electron microscopy (8)(9)(10). In vitro experiments have shown that using purified histones H2A, H2B, H3 and H4, the reconstitution of nucleosomes is possible with polydeoxynucleotides composed of alternating purine- (11,12,13). We are thus prompted to ask the question as to the structural features which allow particular DNA sequences to reconstitute nucleosomes.…”
Section: Introductionmentioning
confidence: 99%
“…This region appears to be devoid of nucleosomes as shown by electron microscopy (8)(9)(10). In vitro experiments have shown that using purified histones H2A, H2B, H3 and H4, the reconstitution of nucleosomes is possible with polydeoxynucleotides composed of alternating purine- (11,12,13). We are thus prompted to ask the question as to the structural features which allow particular DNA sequences to reconstitute nucleosomes.…”
Section: Introductionmentioning
confidence: 99%
“…The following possibilities were suggested [ 5 ] : (a) the presence within each nucleosome of two regions with different thermal stability of DNA, (b) the existence of two structurally different classes of nucleosomes, and (c) the melting of nucleosomal DNA depends on the length of the adjacent spacer regions. The last possibility was ruled out by Bryan et al [12] in experiments with reconstituted histone-DNA complexes. They showed also that the existence of the two transitions could not be explained by DNA compositional differences.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in the response to the thermal exposure is obviously connected with the nature of these transitions. Their origin was recently considered by Staynov [5] and Bryan et al [12]. The following possibilities were suggested [ 5 ] : (a) the presence within each nucleosome of two regions with different thermal stability of DNA, (b) the existence of two structurally different classes of nucleosomes, and (c) the melting of nucleosomal DNA depends on the length of the adjacent spacer regions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations